The rise of domestic popular film production with new audience and changing industry structure: The case of popular cinema in Turkey - ÇETİN ERUS, ZEYNEP (SAGE PUBLICATIONS LTD, 2020)
Transformation of cultural markets is a complex development that relates to both the audience and the industry. During the last decade, domestic popular films in Turkey increased their share of box office significantly. This study analyses socio-economic developments along with monopolization of exhibition sector to understand the change. While factors such as higher income level, relatively lower ticket prices, higher proportion of population in education and urbanization created a new potential audience for domestic films, rise of a dominant player in exhibition sector broke the hegemony created by foreign distribution companies.
Keywords: Box office; film industry; national cinema; new audience; Turkish popular cinema